An ethical reflection on the DOTS programme in South Africa: adherence, vulnerable populations, benefits, and burdens - Maboko, Emmanuel (My University, 2011)
The introduction of the Directly Observed Treatment Short course (DOTS) recommended by the World Health Organization (WHO) in 1991 was developed as the ideal public health measure for the treatment and management of tuberculoisis (TB) (Naidoo, Dick & Cooper 2008:1). However, despite attempts to cure and control tuberculosis, two million new cases are reported in the sub-Saharan region of Africa. The problem of TB in South Africa is made worse by the high incidence and prevalence of HIV/AIDS. There are many contributing factors that may play a part in South Africa’s low cure rate such as unequal national drug distribution, lack of healthcare personnel, patient superstitions and myths concerning tuberculosis. I have touched upon some of these issues. But in this research report I have mainly concentrated on the South African DOTS programme and some of the ethical issues involved in the problem of patient adherence as it concerns the fair societal distribution of burdens and benefits. I have used the ethical framework for public health ethics for my analysis as proposed by Nancy Kass, and also placed a special focus on adherence problems as they concern vulnerable populations. Quality of the DOTS programme in South Africa such as staff attitudes towards TB patients and poor communication skills, nursing care, broken equipment, dirty facilities, absenteeism may contribute towards non-adherence. Moreover, poor quality healthcare services may encourage TB patients to seek alternative treatment other than hospital care thereby increasing their vulnerability to infection and disease progression. Cultural differences in health care and practices may be a barrier to the effective distribution of quality healthcare.
Keywords: Bioethics; Tuberculosis